Absolute vorticity advection and potential vorticity of the free troposphere as synthetic tools for the diagnosis and forecasting of cyclogenesis - Prezerakos, N.G.d; Flocas, H.A.a c; Michaelides, S.C.b (Atmosphere - Ocean, 1997)
The dynamics of a case of cyclogenesis over the central Mediterranean associated with heavy precipitation, especially over the southeast Aegean Sea, have been investigated on the basis of the analyses of two meteorological parameters, namely, the isobaric absolute and relative vorticity and the isentropic potential vorticity. On the whole, the two approaches demonstrate the important role of the upper level dynamics in the initiation of the surface cyclogenesis and seem to identify the same features: interaction of a region of positive absolute vorticity advection ahead of a 500 hPa trough with a shallow frontal system, in the first approach, and an isentropic potential vorticity anomaly at the upper levels with a low level baroclinic zone in the second approach. Furthermore, the analysis of potential vorticity identified an intense low level potential vorticity anomaly, for which there are indications that this is associated with diabatic heating and is important for the deepening of the system. This makes potential vorticity analysis preferable for forecasters. Special emphasis is given to the upper-level circulation and the vorticity field over the major European region before the surface cyclogenesis commences, since it is considered to be crucial for the forecasting of the event.
cited By (since 1996)10